Mahabharata: 4. The Book of Virata, 5. The Book of the Effort - John Britto Chethimattam (Journal of Dharma, 1978)
This is the third volume of Van Buiteneri’s projected single- handed translation of the epic Ma.habharata. With this, more than one third of the great work is complete and the next volume is promised for 1980, volumes five and six by 1983 and the final seventh volume "within a reasonable time thereafter". The Book of Virata sets the stage for the central story of the great epic, the decisive war between the Pandavas and the Kauravas. This preparation for the eighteen days war is done on two levels, a symbolic one in which the Pandava brothers come out victorious in an initial fight against the Kauravas, and a real stage when all possible efforts to settle the dispute peacefully through diplomatic channels are exhausted and war becomes inevitable. The Book of Virata shows the five brothers and their wife Draupati in the service of the cattle.